Prosopography of Teachers' Roles as Change Agents in Riau in the Twentieth Century - Wilaela, Wilaela; Hasbullah, Hasbullah; Zulkifli, Nur Aisyah (SCAD Independent, 2023)
This article analyzes the factors that have contributed to developing teachers' roles as agents of change in Riau in the 20th century. Teachers have played a strategic role in the past and have become an essential group in social and political life. Using the Historical Method and the prosopography approach, 25 biographies of Riau Province figures and the results of interviews with four informants were collected, evaluated, and analyzed. The research findings indicated that the role of teachers in Riau in the 20th century was crucial, and teachers were a productive group that gained trust, recognition, and respect during various periods of struggle in Indonesia. Teachers were able to maximize their role as agents of change due to the following factors: (1) their presence had become an integral part of the cultural and historical journey of Riau society; (2) teachers succeeded in developing their social competence, and their social role became ingrained in the collective memory of society; (3) teachers were intellectual elites with better family backgrounds, education, and experience than the general population; and (4) the dedication, altruistic attitude, and willingness of teachers were reflected in their personalities.